2004
DOI: 10.1016/j.febslet.2004.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an oxaloacetate decarboxylase that belongs to the malic enzyme family

Abstract: The citM gene from Lactococcus lactis CRL264 was demonstrated to encode for an oxaloacetate decarboxylase. The enzyme exhibits high levels of similarity to malic enzymes (MEs) from other organisms. CitM was expressed in Escherichia coli, purified and its oxaloacetate decarboxylase activity was demonstrated by biochemical and genetic studies. The highest oxaloacetate decarboxylation activity was found at low pH in the presence of manganese, and the K m value for oxaloacetate was 0.52 % 0.03 mM. However, no mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Oxaloacetate decarboxylase of L. lactis encoded by the mae gene belongs to the second group, and no OAD genes are carried on the chromosome. The mae gene product of L. lactis is the only soluble oxaloacetate decarboxylase that has been characterized in detail (25). The deletion mutant was created by a frameshift deletion of 14 bp between positions 584 and 598 in the gene (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxaloacetate decarboxylase of L. lactis encoded by the mae gene belongs to the second group, and no OAD genes are carried on the chromosome. The mae gene product of L. lactis is the only soluble oxaloacetate decarboxylase that has been characterized in detail (25). The deletion mutant was created by a frameshift deletion of 14 bp between positions 584 and 598 in the gene (1).…”
Section: Discussionmentioning
confidence: 99%
“…Following uptake by the secondary citrate transporter CitP, citrate lyase (CL) converts citrate to acetate and oxaloacetate. Acetate is not further metabolized and leaves the cells, while oxaloacetate is decarboxylated to pyruvate by a soluble oxaloacetate decarboxylase encoded by the mae gene and termed CitM (25). In a recent study it was demonstrated that in the lactic acid bacterium Lactococcus lactis IL1403(pFL3), part of the pyruvate formed from citrate was converted into acetoin and part was converted into acetate in parallel pathways (23).…”
mentioning
confidence: 99%
“…Therefore, like for malolactic fermentation, the proton motive force-generating system is built around a precursor/product exchanger (CitP) and a decarboxylase (CitM). The latter was recently shown to be a member of the malic enzyme family, to which malolactic enzyme (MleS) and the oxidative malate decarboxylase (MalS) also belong (129). The oxaloacetate decarboxylases are closely related to the MalS type of malic enzymes, which decarboxylate malate to pyruvate.…”
Section: Physiological Functionmentioning
confidence: 99%
“…NAD ϩ /NADH was shown to be nonessential to the oxaloacetate decarboxylation activity. Nevertheless, the cofactor binding site appears to be conserved in the CitM proteins, and the ability to bind NAD ϩ and NADH was demonstrated by inhibition of enzyme activity in their presence (129).…”
Section: Physiological Functionmentioning
confidence: 99%
“…The malic enzyme catalyzes oxaloacetate decarboxylation as the second partial reaction in the conversion of malate to CO 2 plus pyruvate with the reduction of NAD to NADH (41). CitM within the malic enzyme family has evolved to function in a specialized citrate degradation pathway in a small group of Gram-positive bacteria (42). The CitM cannot convert malate to oxaloacetate but it does decarboxylate oxaloacetate at an efficiency of k cat = 20 s −1 and K m = 0.5 mM using the same catalytic residues of the malic enzyme.…”
Section: Pa4872 Catalytic Mechanismmentioning
confidence: 99%